Emotional programmes through yoga in early childhood education motor skills session: A narrative review - Roldán Vicent, Susana; González Valero , Gabriel; Cachón Zagalaz, Javier (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Spanish legislation has recently incorporated the term emotional education, implying the need for a change of focus where emotions take on greater prominence. The scientific literature in the field of education highlights the suitability of the use of physical activity and yoga as tools for the development of emotional education. The aim of this study was to carry out a narrative review of the use of these resources to address quality emotional education in early childhood education. After carrying out a state of the question, the study showed that teacher training in this regard is insufficient, despite the fact that more and more professionals are deciding to include the practice of yoga in their classrooms. More research is therefore needed to equip teachers with the necessary knowledge to provide quality emotional education through physical activity and yoga.